2019
DOI: 10.1101/657817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gap junctions in theC. elegansnervous system regulate ageing and lifespan

Abstract: The nervous system is a central regulator of longevity, but how neuronal communication interfaces with ageing pathways is not well understood. Gap junctions are key conduits that allow voltage and metabolic signal transmission across cellular networks, yet it has remained unexplored whether they play a role in regulating ageing and longevity. We show that the innexin genes encoding gap junction subunits in Caenorhabditis elegans have extensive and diverse impacts on lifespan. Loss of the neural innexin unc-9 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…The innate immune response induced by bacterial infection occurs primarily in the gut ( 6 ) or epidermal tissue ( 11 ) of C. elegans . Remarkably, inx-14 is mainly expressed in the germline, neurons and muscle cells ( 34 , 40 ). To determine in which tissue inx-14 acts to reduce intestinal defense, we treated animals with tissue-specific inx-14 RNAi prior to PA14 infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The innate immune response induced by bacterial infection occurs primarily in the gut ( 6 ) or epidermal tissue ( 11 ) of C. elegans . Remarkably, inx-14 is mainly expressed in the germline, neurons and muscle cells ( 34 , 40 ). To determine in which tissue inx-14 acts to reduce intestinal defense, we treated animals with tissue-specific inx-14 RNAi prior to PA14 infection.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate that inx-14 , a heterotypic and heteromeric gap junction subunit, suppresses intestinal defense, as mutants lacking this gene showed strongly increased resistance to PA14 infection. Recent studies have demonstrated that INX-14 is widely expressed in the germline, neurons and muscle ( 34 , 40 ). To determine the tissue in which INX-14 functions, we performed tissue-specific RNAi and rescue assays and remarkably found that INX-14 primarily acts in the germline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation